Decoding the Natural Killer Cell Enigma: A Review - Gamde, Solomon Matthias; Michelle, Ogidiagba Stephanie; Abriba, Simon Peter; Banda, Jim M; Adisa, James O (International Journal of Human and Health Sciences (IJHHS), 2024)
Background: While the liver’s hepatocytes and Kupffer cells are prominent foci of study, the distinct and relatively uncharted roles played by the natural killer cells in liver immunity provide fertile ground for exploration. In this review paper, we have tried to uncover the unique phenotypic and functional attributes of liver-resident natural killer cells, consequently establishing a profound connection between liver immunology and histopathology. Objective: This review aims to provide an overview of the phenotypic and functional properties of the liver-resident natural killer cells, giving insight on the immunological and histological repercussions of their interactions during liver infections, inflammation, and hepatocellular cancer. Methods: In this review, published papers in electronic databases comprising PubMed, Scopus, and Google Scholar were retrieved using search themes such as immunological cells, natural killer cell, liver inflammation, and liver cell were examined. Results: The liver-resident natural killer cells are potent producers of cytokines, including interferon-gamma (IFN-γ) and modulate the phenotype and function of hepatic macrophages, enhancing their antimicrobial activity, as well as influence the activation and cytotoxic function of CD8+ T cells, particularly during chronic liver inflammation. Conclusion: Our review underscores the undeniable significance of the natural killer cells in the liver defence and highlighted the challenges and constraints researchers encounter when studying the liver natural killer cells. Continued research endeavour are necessary to harness the full capabilities of the natural killer cells, ultimately leading to better insights, innovative therapies, and enhanced protection for the liver, and by extension, the entire body. International Journal of Human and Health Sciences Vol. 08 No. 03 Jul’24 Page: 231-240